Chloroplast Diversity and Phylogeny in Wild and Cultivated Rice (Oryza spp.) - Siriporn Chuayjaeng,; Hugo Volkaert, (Agriculture and Natural Resources, 2006)
Genetic diversity was studied in the chloroplast genome of wild and cultivated rice, especially in species belonging to the A genome group, to clarify the phylogenetic relationships in Oryza. Specific DNA fragments were PCR-amplified from 140 accessions of cultivated and wild rice and investigated by restriction analysis and SSCP (PCR-RF-SSCP or PRS). After the SSCP patterns were scored, amplified fragments from representative accessions of each observed SSCP pattern were sequenced. Haplotypes of cultivated rice and closely related wild relatives (A genome) were more similar than those of distantly related species (B, C/CD, E and G genomes). The polymorphisms were due to insertion/deletion (indels) and nucleotide substitutions. Substitutions and indels at ORF100, and rpoA locus could separate the Asian cultivated rice indica type from japonica type. Additional substitutions and indels at all four cpDNA loci could separate the rice species with the AA genome from those belonging to other genomes (but these mutations were not congruent with indica/japonica division). Within the AA genome four groups could be separated, Asian wild rice with Asian cultivated rice, O. glumaepatula group, African wild rice with African cultivated rice (O. glaberrima) and O. meridionalis group.